Analisis Implementasi Metode Pembelajaran Salafi dan Modern terhadap Hasil Belajar Santri di Kabupaten Tangerang Banten - Putra, Ayang Aji; Wasehudin; Lazzavietasmi, Fandy Adpen; Supardi; Bachtiar, Machdum (Lembaga Teewan Journal Solutions, 2026)
Islamic boarding schools (pondok pesantren) are one of the non-formal educational institutions spread throughout Indonesia, having emerged within society itself. Generally, Islamic boarding schools can be classified into two types: salaf (traditional) Islamic boarding schools and khalaf (modern) Islamic boarding schools. The purpose of this study is to determine the implementation of salafi and modern teaching methods on the learning outcomes of students (santri) in Tangerang Regency, Banten, by conducting research at An-Nur Islamic Boarding School and As-Syifa Al-Falahiyah Banu Hamim Islamic Boarding School. This study uses a qualitative approach, namely an approach aimed at deeply and holistically understanding social phenomena through descriptive data collection processes. The results of this study are as follows: First, the implementation of salafi and modern teaching methods applied in the educational and teaching processes at An-Nur Islamic Boarding School and As-Syifa Al-Falahiyah Banu Hamim Islamic Boarding School. Second, the strengths and weaknesses of both salafi and modern teaching methods, which make their collaboration into a unified whole that mutually complements and strengthens the teaching and educational process within the Islamic boarding school environment. Third, the evaluation of salafi and modern teaching methods. The evaluation applied to the salafi method varies widely, such as tests on reading the kitab kuning (yellow books), assignments to lead dzikir (remembrance) tahlil, and memorization tests of verses/lines (bait-bait) from the subject matter contained in the kitab kuning using nadzom (poetic didactic verses). Meanwhile, the evaluation of modern teaching methods includes oral and written examinations in each semester, speech contests in Arabic and English, and examinations of computer-based learning materials—often referred to as CBT (Computer Based Test). Then, the results from all stages of implementing the salafi and modern teaching methods at An-Nur Islamic Boarding School and As-Syifa Al-Falahiyah Banu Hamim produce effectiveness for every student, covering the cognitive, affective, and psychomotor domains.